Intradialytic aerobic training improves inflammatory markers in patients with chronic kidney disease: a randomized clinical trial - Lucas Gonçalves da Cruz; Hugo Ribeiro Zanetti; Alynne Christian Ribeiro Andaki; Gustavo Ribeiro da Mota; Octávio Barbosa Neto; Edmar Lacerda Mendes (Universidade Estadual Paulista (UNESP), 2018)
Abstract Aims: To investigate the effect of 12 weeks of intradialytic aerobic training on serum levels of interleukin-1β, interleukin-6, interleukin-8, interleukin-10, tumor necrosis factor alpha and functional capacity. Methods: Thirty sedentary volunteers were randomly assigned to either to exercise or control group. Exercise group were submitted to 12 weeks of aerobic training performed on a cycle ergometer for 30 minutes at intensity rated using the Borg scale (6 to 7) three times a week while control group kept the daily habits. Results: After 12 weeks only exercise group presented a significant reduction of serum levels of interleukin-1β, interleukin-6, interleukin-8, tumor necrosis factor alpha and an increase in serum levels of interleukin-10 and functional capacity. Conclusion: Twelve weeks of intradialytic aerobic training was effective in controlling inflammation and improving the functional ability of patients with chronic kidney disease.